2012
DOI: 10.1161/atvbaha.112.248559
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme 2 Contributes to Sex Differences in the Development of Obesity Hypertension in C57BL/6 Mice

Abstract: Objective Obesity promotes hypertension, but it is unclear if sex differences exist in obesity-related hypertension. Angiotensin converting enzyme 2 (ACE2) converts angiotensin II (AngII) to angiotensin-(1–7) (Ang-[1–7]), controlling peptide balance. We hypothesized that tissue-specific regulation of ACE2 by high-fat (HF) feeding and sex hormones contributes to sex differences in obesity-hypertension. Methods and Results HF-fed females gained more body weight and fat mass than males. HF-fed males exhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
215
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(233 citation statements)
references
References 40 publications
9
215
6
Order By: Relevance
“…17␤-Estradiol (E 2 ) has been reported to regulate ACE2 expression both in vitro and in vivo (15,20,21). Moreover, results from our laboratory demonstrated that E 2 increases ACE2 mRNA abundance in adipocytes (15).…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…17␤-Estradiol (E 2 ) has been reported to regulate ACE2 expression both in vitro and in vivo (15,20,21). Moreover, results from our laboratory demonstrated that E 2 increases ACE2 mRNA abundance in adipocytes (15).…”
mentioning
confidence: 93%
“…Ovariectomy of HF-fed female mice reduced adipose ACE2 expression and plasma ANG-(1-7) concentrations and converted female mice to an obesity-hypertension phenotype (15). These results suggest that sexual dimorphism of obesity-hypertension may be associated with ACE2-mediated regulation of the ANG II/ANG-(1-7) balance, and that adipose ACE2 may contribute significantly to regulation of the balance of these vasoactive peptides.17␤-Estradiol (E 2 ) has been reported to regulate ACE2 expression both in vitro and in vivo (15,20,21). Moreover, results from our laboratory demonstrated that E 2 increases ACE2 mRNA abundance in adipocytes (15).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…disease (17). Further studies exploring the relationship between epicardial adipose tissue, the RAAS, and cardiomyopathy in female models of obesity may shed light on why heart failure with a preserved ejection fraction is more common in obese women.…”
mentioning
confidence: 98%